PROXIMATE COMPOSITION, HEAVY METAL CONTENT AND MACROELEMENT PROFILE OF CHICKEN FEED SUPPLEMENTS FROM Egeria radiata(CLAM) AND Tympanotonus fuscatus (PERIWINKLE) SHELLS - Esu, Ubong A.; Orji, Blessing O.; Etim, Oboso E.; Ekpo, Ndifreke D.; Bassey, Utibe E.; Ndem, Jessie I. (FUDMA Journal of Sciences, 2026)
Poultry farming relies on feed supplements to maximize .growth by providing nutrients which may be lacking in their basic diets. This study evaluated the nutritional composition and safety characteristics of mollusk shell powders from Egeria radiata (clam) and Tympanotonus fuscatus (periwinkle) as alternative calcium supplements for poultry feed. Clams and periwinkles were collected from Ishiet River in Akwa Ibom State, processed into fine powder, and subjected to comprehensive proximate analysis, macroelements composition and heavy metal screening following standard methods. Results revealed that shell supplements exhibited predominant mineral composition with significant (p < 0.05) elevated ash content, relative to standard feed. Calcium and potassium content were also significantly (p < 0.05) higher in the shells compared to standard feed. T. fuscatus shells demonstrated significantly (p < 0.05) elevated iron content in comparison to E. radiata and feed. Heavy metal concentrations were below WHO/FAO permissible limits, with no detectable cadmium.  Shell supplements demonstrated significantly (p < 0.05) low moisture content, and protein levels, likely representing residual organic matrix proteins. From the findings, it can be concluded that shell preparations had favourable compositional and safety characteristics. Nevertheless, controlled feeding trials remain essential for validating biological efficacy, establishing optimal inclusion rates, and assessing long-term performance outcomes in commercial poultry production systems.
Keywords: Egeria radiata; Heavy metals; Macroelement composition; Poultry nutrition; Proximate composition; Tympanotonus fuscatus